2021
DOI: 10.3389/fmed.2021.742419
|View full text |Cite
|
Sign up to set email alerts
|

T-Lymphocyte Subsets Alteration, Infection and Renal Outcome in Advanced Chronic Kidney Disease

Abstract: Background: T-lymphocyte subsets reflect patients' immune status and are associated with adverse outcomes in various diseases. However, the association between T-lymphocyte subsets and major infection and renal outcome in chronic kidney disease (CKD) patients has not been well-addressed.Methods: Patients diagnosed with stage 3–5 of non-dialysis CKD were recruited, and healthy subjects were selected as the controls. T-lymphocyte subsets (CD3+, CD4+, CD8+) were detected by flow cytometry, and the CD4+/CD8+ T cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 46 publications
4
9
0
Order By: Relevance
“…So, the increase of Th17 cells in NMO patients did not mean the increase of the total CD4 + T cells and CD4/CD8. Xiong et al [32] found that CD4 + T cells and CD4/CD8 were significantly decreased in chronic kidney disease, and Wang et al [33] found decreased CD4 + T cells and CD4/CD8 ratio in systemic lupus erythematosus, which support our ideas. However, we still need a deeper understanding of T-cell immunophenotyping.…”
Section: Discussionsupporting
confidence: 88%
“…So, the increase of Th17 cells in NMO patients did not mean the increase of the total CD4 + T cells and CD4/CD8. Xiong et al [32] found that CD4 + T cells and CD4/CD8 were significantly decreased in chronic kidney disease, and Wang et al [33] found decreased CD4 + T cells and CD4/CD8 ratio in systemic lupus erythematosus, which support our ideas. However, we still need a deeper understanding of T-cell immunophenotyping.…”
Section: Discussionsupporting
confidence: 88%
“…It has been shown that a significant reduction in T-cell subsets, particularly CD4 + and CD8 + subsets, in the CKD population is a critical factor in the exacerbation of CKD. [65,66] In the present study, JUND was shown to be significantly and positively correlated with T cell CD8 + subpopulations, suggesting that JUND may promote the expression of T cell CD8 + subpopulations to reduce the progression of CKD. In the current investigation, a significant positive correlation was observed between AFF1, ZFP36L1, and M2 macrophages, indicating that AFF1 and ZFP36L1 potentially contribute to the upregulation of M2 macrophage expression in CKD.…”
Section: Discussionsupporting
confidence: 57%
“…External application of traditional Chinese medicine for promoting blood circulation and removing stasis in arteriovenous fistula can not only improve subcutaneous hematoma and promote the dissipation and absorption of hematoma but also prevent the occurrence of stenosis and occlusion of arteriovenous fistula. Studies have suggested that T lymphocyte subsets may change significantly in patients with end-stage renal disease, with significantly reduced levels of CD3+, CD4+, and CD8+T lymphocytes [ 16 ]. The results of this study suggest that the levels of CD3+, CD4+, and CD8+T lymphocytes also play an important role in the occurrence and development of arteriovenous fistula stenosis.…”
Section: Discussionmentioning
confidence: 99%